Oxidative stress-induced stress granules: a central link to protein aggregation in neurodegenerative diseases - Younas, Neelam; Zerr, Inga (Frontiers in Neuroscience, 2025)
Intracellular aggregation of proteins such as Tau, TDP43, FUS, prion protein, and α-synuclein is a major hallmark of many major neurodegenerative diseases. Aberrant stress granules (SGs) are emerging as key contributors to the nucleation of toxic protein aggregates in these disorders. SGs are dynamic, membrane less cytoplasmic assemblies that form transiently through liquid–liquid phase separation (LLPS) of RNA binding proteins (RBPs) containing low complexity domains, together with stalled mRNAs, to help cells cope with stress. While physiological SGs facilitate cellular resilience to acute stress and undergo rapid disassembly, chronic or excessive stress leads to persistent SGs, driving pathological protein aggregation characteristic of age related neurodegeneration. The inherent reversible aggregation of RBPs crucial for cellular function paradoxically exposes them to misfolding disorders. Notably, recent findings expand this paradigm by demonstrating that Tau itself participates in SG formation, with Tau–SG interactions potentiating Tau aggregation and disease progression in tauopathies. Despite these insights, the precise cellular stressors and posttranslational modifications (PTMs) governing the shift from physiological granules to pathological aggregates remain poorly defined. Emerging evidence highlights oxidative stress as a central upstream mediator of this transition. In this perspective, we synthesize current understanding of how SG dynamics intersect with oxidative stress to potentiate protein aggregation, proposing molecular mechanisms that bridge SG biology and neurodegenerative disease. Elucidating these pathways is essential for the development of targeted therapeutic interventions for disorders such as Alzheimer’s disease and related tauopathies.